The Impact of Ride-Hailing Platforms on the Livelihoods and Social Welfare of Gig Economy Workers in Indonesia - Ratu Agung Bagus Ngurah Putra; Nandar Hlaing; Sevda Kara (Yayasan Adra Karima Hubbi, 2025)
The rise of ride-hailing platforms has significantly transformed the labor market in Indonesia, especially within the gig economy. As a rapidly growing sector, these platforms offer flexible work opportunities, attracting millions of workers. However, the impact of ride-hailing on the livelihoods and social welfare of gig economy workers remains understudied. This research aims to explore how ride-hailing platforms influence the income stability, social security, and overall well-being of gig workers in Indonesia. A mixed-methods approach was used for this study, combining surveys and in-depth interviews with 300 gig workers from major cities like Jakarta, Surabaya, and Yogyakarta. The survey collected quantitative data on income patterns, job satisfaction, and access to social benefits, while qualitative interviews provided deeper insights into the social and psychological effects of gig work. The findings indicate that while ride-hailing platforms offer a source of income and flexible working hours, they also expose workers to income instability, lack of social protection, and job insecurity. Only 15% of workers reported having access to formal social security benefits, with many relying on informal networks for support. Additionally, mental health concerns were prevalent due to the unpredictable nature of gig work and the absence of a supportive work environment. The study concludes that while ride-hailing platforms offer significant economic opportunities, there is an urgent need for policy reforms that address workers' rights, social security, and job security to ensure the sustainability of their livelihoods and well-being.